Characterization of cell wall structure in dilute acid-pretreated biomass by confocal Raman microscopy and enzymatic hydrolysis. (October 2016) - Na, Byeong-Il; Chang, Sung-Jin; Lee, Kwang Ho; Lee, Gaehang; Lee, Jae-Won
Abstract: The chemical and ultrastructural properties of cell walls were investigated to determine the effect of dilute acid pretreatment on the hydrolysis of lignocellulosic biomass. Confocal Raman microscopy was used to gain a clear understanding of how dilute acid pretreatments destroy lignocellulosic cell walls. Total fermentable sugar (glucose and xylose) was high in oxalic acid hydrolysate (26.18 g/L) compared to that in sulfuric acid hydrolysate (24.34 g/L). Chemical composition of the pretreated biomass differed slightly according to the acid catalyst used. Oxalic acid pretreatment was effective for enzymatic hydrolysis, with 29.46 g/L of total fermentable sugar after 96 h. Optical microscopy showed that dilute acid pretreatment significantly changed cell wall structure, and broken and crushed cell walls could be clearly seen during pretreatment. Based on confocal Raman peak intensity, the ratio of lignin/cellulose [I(1600)/I(900)] was low for oxalic acid-pretreated biomass compared to sulfuric acid-pretreated biomass. Highlights: Confocal Raman microscopy was used to understand effect of dilute acid pretreatment. Total fermentable sugar in oxalic acid hydrolysate was high as 26.18 g/L. Dilute acid pretreatment significantly changed cell wall structure. The ratio of lignin/cellulose [I(1600)/I(900)] was low for oxalic acid-pretreated biomass.